2022
DOI: 10.3390/jcm11123275
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Training in Post-COVID-19 Persistent Olfactory Disorders: Value Normalization for Threshold but Not Identification

Abstract: (1) Background: Persistent post-viral olfactory disorders (PPVOD) are estimated at 30% of patients one year after COVID-19 infection. No treatment is, to date, significantly effective on PPVOD with the exception of olfactory training (OT). The main objective of this work was to evaluate OT efficiency on post-COVID-19 PPVOD. (2) Methods: Consecutive patients consulting to the ENT department with post-COVID-19 PPVOD were included after completing clinical examination, the complete Sniffin’ Stick Test (TDI), the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 64 publications
2
17
0
1
Order By: Relevance
“…To date, there are only a few studies investigating the efficacy of olfactory training in the treatment of post-COVID-19 persistent OD. A recent study by Vandersteen and colleagues [24] reported a significant clinical recovery after OT in patients with COVID-19-related persistent OD. Their cohort was comprised of forty-three patients with a mean OD duration of 5.8 ± 3.2 months.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To date, there are only a few studies investigating the efficacy of olfactory training in the treatment of post-COVID-19 persistent OD. A recent study by Vandersteen and colleagues [24] reported a significant clinical recovery after OT in patients with COVID-19-related persistent OD. Their cohort was comprised of forty-three patients with a mean OD duration of 5.8 ± 3.2 months.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding the effectiveness of OT across three different olfactory abilities-smell identification, discrimination, and threshold-several meta-analyses [10,11,20] reported a great variance in the improvement of these subscores. In patients with post-COVID-19 persistent OD who performed OT, Vandersteen and colleagues [24] observed a significant T and I improvement, followed by a non-significant D improvement. Our study, however, produced a significant increase in the mean values of all subsets of the Sniffin' Sticks test after the COT.…”
Section: Discussionmentioning
confidence: 96%
“… 16 17 Contrary to the findings of our study, a recent report indicated that the C19OD patient group included a high percentage of women. 18 19 20 Heo et al reported that patients who recovered were mostly women ( P =0.001) who were significantly younger ( P = 0.048). 20 Considering that the average duration of symptoms in the C19OD patient group who visited our hospital was more than four months, selection bias may have occurred because of the high proportion of men who did not recover from the symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Hummel et al 6 reported a significant effect only on the T-score after olfactory training, and Sorokowska et al 8 reported significant effects on the D, I, and TDI total scores, excluding the T-score. Vandersteen et al 19 reported a significant increase in the T score and decrease in the D score after olfactory training in patients with C19OD, suggesting the need for a study on the etiology of the central abnormality of C19OD. Although there are differences among papers on the exact effect of olfactory training, olfactory training was introduced as a good treatment method without side effects even in C19OD.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 A positive effect of olfactory training (OT) on the recovery from post-infectious olfactory disorders has already been shown in studies. 19 - 21 This study aims to compare these two therapeutic approaches to the treatment of persistent olfactory dysfunction. Most data on loss of smell rely on the evaluation of orthonasal olfactory performance.…”
Section: Introductionmentioning
confidence: 99%